(untitled) (Prithvi Academic Journal, 2019)
This paper examines how humans’ chauvinistic attitudes and behavior toward nonhumans exist in humans’ orality in the course of analyzing some selected Nepali proverbs. The proverb as a powerful form of the oral literature can transmit the message and meaning to both literate and illiterate people virtually. Anthropocentrism, one of the approaches of ecocriticism that largely discusses human-nonhuman relationships skewing to humans, has been applied as theoretical insight to expose how humans have overlooked the intrinsic values of nonhumans. While analyzing, humans appear to behave as the sole proprietors of the whole nature by exploiting nonhumans as resources and seem to reject those nonhumans, which they fail to capitalize on. Finally, it could be inferred through this scrutiny that humans look sharply experienced to calculate profit, mostly untrained to comprehend the role of nonhumans in this ecosystem, and muscularly versed to dishonor nonhumans’ loyalty to humans as their weakness.